Secret files of the Inquisition. Episode IV, The end of Inquisition - Rabinovitch, John David; Allcock, Michael; Feore, Colm, 1958-; Inquisition Productions, Inc.; Soundview Media Partners ([Canada?] : Inquisition Productions, Inc., 2006)
In 1858, Pope Pius IX orders the Inquisitor of Bologna to take a six-year-old Jewish boy, Edgardo Mortara, from his family after he learns that the boy had been secretly baptized. In the political turmoil that follows, the Pope becomes a virtual prisoner in the Vatican and the once powerful Holy Roman Empire is reduced to just one hundred acres.
Screenwriter's name should read Michal Allcock.
Originally broadcast on television in 2006.
Michael Alcock should read Michael Allcock.
Narrator: Colm Feore.
Director of photography, Pieter Stathis ; editor, Paul Tourneur ; music, John Sereda & Mike Thomas.
In English.
Keywords: Catholic Church -- History; Inquisition; Documentary television programs; Historical television programs; Historical reenactments (Television programs); Television mini-series.; Nonfiction television programs; Internet videos; Streaming video